2016
DOI: 10.1007/s13205-016-0398-6
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive metabolites produced by Streptomyces Cheonanensis VUK-A from Coringa mangrove sediments: isolation, structure elucidation and bioactivity

Abstract: The strain VUK-A was isolated from a sediment sample of the Coringa mangrove ecosystem was identified as Streptomyces cheonanensis based on morphological, physiological, biochemical and molecular properties. Chemical investigation of the secondary metabolites of the strain Streptomyces cheonanensis VUK-A has led to the segregation of two bioactive compounds, namely 2-Methyl butyl propyl phthalate (1) and Diethyl phthalate (2) using column chromatography. The chemical structure of the active compounds was estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 30 publications
3
27
0
Order By: Relevance
“…Ilayaraja et al (2014) reported that zones of inhibition exhibited by antimicrobials from actinomycetes were determined by the strains of the actinomycetes from which they were obtained. However, Mangamuri et al, (2016) pointed that the environment in which the actinomycetes grow determines their biochemical activities, a factor that influences the types of the produced antimicrobials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ilayaraja et al (2014) reported that zones of inhibition exhibited by antimicrobials from actinomycetes were determined by the strains of the actinomycetes from which they were obtained. However, Mangamuri et al, (2016) pointed that the environment in which the actinomycetes grow determines their biochemical activities, a factor that influences the types of the produced antimicrobials.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, actinomycetes are the leading producers of antitumor agents, enzymes, immunosuppressive agents, antifungals, neurigenics, antioxidants, anti-helmitics, anti-malarials, anti-algals, and anti-inflammatory agents (Mangamuri et al, 2016). Currently, researchers are targeting the use of antibiotics from actinomycetes in other areas such as boosting immunity in AIDS and Alzheimer diseases, in addition to their use as ant-ageing agents (Bandari et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…were isolated by serially diluting the pretreated rhizosphere soil sample and inoculating by spread plate method onto various agar medium recommended for Actinomycetes spp. such as glycerol asparagine agar, actinomycetes isolation agar (Nanjwade et al, 2010), tryptone yeast extract medium (ISP1), yeast extract malt extract agar (ISP2) (Busarakam et al, 2014) and Czapek dox agar (Mangamuri et al, 2016). The media were supplemented with gentamicin (1 μg/ml) and fluconazole (50 μg/ml) after sterilization to inhibit the growth of bacteria and fungi, respectively (Eccleston et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Anti-candida activities against C. albicans ATCC 10231 have been reported for metabolites produced by Pseudonocardia endophytica VUK-10 [24], S. cheonanensis VUK-A [25] (India), and Micromonospora sp. strain G019 [26] (Vietnam).…”
Section: Bacteria From Marine Sedimentsmentioning
confidence: 99%